The Role of Heat Shock Proteins in Type 1 Diabetes - Moin, Abu Saleh Md; Nandakumar, Manjula; Diane, Abdoulaye; Dehbi, Mohammed; Butler, Alexandra E. (Frontiers in Immunology, 2021)
Type 1 diabetes (T1D) is a T-cell mediated autoimmune disease characterized by recognition of pancreatic β-cell proteins as self-antigens, called autoantigens (AAgs), followed by loss of pancreatic β-cells. (Pre-)proinsulin ([P]PI), glutamic acid decarboxylase (GAD), tyrosine phosphatase IA-2, and the zinc transporter ZnT8 are key molecules in T1D pathogenesis and are recognized by autoantibodies detected in routine clinical laboratory assays. However, generation of new autoantigens (neoantigens) from β-cells has also been reported, against which the autoreactive T cells show activity. Heat shock proteins (HSPs) were originally described as ‘cellular stress responders’ for their role as chaperones that regulate the conformation and function of a large number of cellular proteins to protect the body from stress. HSPs participate in key cellular functions under both physiological and stressful conditions, including suppression of protein aggregation, assisting folding and stability of nascent and damaged proteins, translocation of proteins into cellular compartments and targeting irreversibly damaged proteins for degradation. Low HSP expression impacts many pathological conditions associated with diabetes and could play a role in diabetic complications. HSPs have beneficial effects in preventing insulin resistance and hyperglycemia in type 2 diabetes (T2D). HSPs are, however, additionally involved in antigen presentation, presenting immunogenic peptides to class I and class II major histocompatibility molecules; thus, an opportunity exists for HSPs to be employed as modulators of immunologic responses in T1D and other autoimmune disorders. In this review, we discuss the multifaceted roles of HSPs in the pathogenesis of T1D and in autoantigen-specific immune protection against T1D development.